PENGARUH FASILITAS SEKOLAH DAN PERHATIAN ORANG TUA TERHADAP HASIL BELAJAR MELALUI DISIPLIN BELAJAR DAN MINAT BELAJAR SEBAGAI VARIABEL INTERVENING DI SMK CERSA PASAMAN: Penelitian Deskriptif - Yola Isdayanti; Lovelly Dwinda Dahen; Vivina Eprillison (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to describe the influence of school facilities and parental attention on learning outcomes through discipline and interest in learning as intervening variables at Cersa Pasaman Vocational School 1) the influence of school facilities on learning outcomes, 2) the influence of school facilities through learning discipline as an intervening variable on learning outcomes, 3) the influence of school facilities through learning interest as an intervening variable on learning outcomes, 4) the influence of parental attention on learning outcomes, 5) the influence of parental attention through learning discipline as an intervening variable on learning outcomes, 6) the influence of parental attention through learning interest as an intervening variable on learning outcomes, 7) the influence of learning discipline on learning outcomes, 8) the influence of learning discipline through interest in learning as an intervening variable on learning outcomes, 9) the influence of interest in learning on learning outcomes, 10) the influence of interest in learning through learning discipline as an intervening variable on learning outcomes.This type of research is associative. The population in this study were students in classes X and XI at Cersa Pasaman Vocational School, totaling 93 people. Sampling used total sampling technique. The instrument used for the research was a closed questionnaire using path analysis and hypothesis testing using the t test.